An Analysis of Reduction Technique Applied on the Interrogative Sentences and Its Impact on the Translation Quality in the Movie Subtitle of National Treasure 2: Book of Secret - Siti Noor aisyiyah (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
This research is conducted to analyze the use of reduction technique on interrogative sentences in the movie subtitle of National Treasure 2: Book of Secret. The objectives of this research are (1) to find out the types of reduction technique in translating interrogative sentences in the movie subtitle of National Treasure 2: Book of Secret: (2) to find out the accuracy and acceptability of the interrogative sentences that are translated using reduction technique in the movie subtitle of National Treasure 2: Book of Secret as a result of the reduction technique application.This research is a descriptive qualitative research. The data consist of interrogative sentences with reduction technique that are found in the movie subtitle National Treasure 2: Book of Secret and the statement from the informants about the quality of the translation. The sampling techniques are total sampling and a purposive sampling technique.The result of this study shows that there are 62 data (52.54%) accurate, 51 data (43.22%) less accurate, and five data (4.23%) inaccurate. The current study also shows that there are 111 data (94.06%) classified into acceptable translations and seven (5.93%) classified into less acceptable translations. Keywords: reduction, reduction techniques, translation quality.